Secular trends of cardiorespiratory fitness in children and adolescents over a 35-year period: Chronicle of a predicted foretold - Leone, Mario; Levesque, Patrick; Bourget-Gaudreault, Sabrina; Lemoyne, Jean; Kalinova, Emilia; Comtois, Alain Steve; Bui, Hung Tien; Léger, Luc; Frémont, Pierre; Allisse, Maxime (Frontiers in Public Health, 2023)
Background: In the context of concerns regarding the cardiorespiratory fitness (CRF) of youth populations, the aims of this study were: 1) to update reference values for the VO2peak for school-aged Canadians and 2) to document secular trends in CRF after a 35-year interval. Methods: Between September 2014 and April 2017, the CRF of 3725 students (53.2% boys; 6.0 to 17.9 yrs) was determined using the 20-m shuttle run test validated by Léger and colleagues (1984). The sample was collected in 36 different schools from six cities of Québec (Canada). Results: Median values of VO2peak decreased with age in both sexes (p≤0.05). By the age of 10, more than 20% of boys showed VO2peak values below the recommended value (42 ml·kg-1·min-1). At the age of 17, that proportion reached 56.8%. A similar proportion of 12 yrs girls (20%) were under the recommended minimal value (37 ml·kg-1·min-1) and that value reached 69.9% at the age of 17. Compared to 1982, the VO2peak at age 17 has declined by 18% for boys and 12% for girls. The situation is worse in terms of functional capacity (number of stages completed) with an overall decrease of more than 30%. Conclusion: This study demonstrates that, compared to data obtained using the same methodology 35 years ago, the CRF and functional capacity of children and adolescents has declined to levels that should raise concerns from a public health perspective. Thus, the development of strategies to promote a physically active lifestyle in youth is more relevant than ever.